The year the Gypsies came - Glass, Linzi (London : Penguin Books, 2007)
In Johannesburg, South Africa, in the late 1960s, twelve-year-old Emily, who longs for affection from her quarreling parents, finds comfort in the stories of a Zulu servant and in her friendship with young houseguest who has an equally troubled family.
Keywords: Problem families -- Fiction; South frica -- History -- Fiction. -- 20th century